Systematic Theoretical Analysis of Dual-Parameters RF Readout by a Novel LC-Type Passive Sensor. (13th March 2017) - Tan, Qiulin; Guo, Yanjie; Wu, Guozhu; Luo, Tao; Wei, Tanyong; Shen, Sanmin; Zhang, Wendong; Xiong, Jijun
Abstract : This paper systematically studied the simultaneous measurement of two parameters by a L C -type passive sensor from the theoretical perspective. Based on the lumped circuit model of the typical L C -type passive dual-parameter sensor system, the influencing factors of the signal strength of the sensor as well as the influencing factors of signal crosstalk were both analyzed. It is found that the influencing factors of the R F readout signal strength of the sensor are mainly quality factors (Q factors) of the L C tanks, coupling coefficients, and the resonant frequency interval of the two L C tanks. And the influencing factors of the signal crosstalk are mainly coupling coefficient between the sensor inductance coils and the resonant frequency interval of the two L C tanks. The specific influence behavior of corresponding influencing factors on the signal strength and crosstalk is illustrated by a series of curves from numerical results simulated by using MATLAB software. Additionally, a decoupling scheme for solving the crosstalk problem algorithmically was proposed and a corresponding function was derived out. Overall, the theoretical analysis conducted in this work can provide design guidelines for making the dual-parameter L C -type passive sensor useful in practical applications.